1999
DOI: 10.2337/diacare.22.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Increased intimal-medial thickness in newly detected type 2 diabetes: risk factors.

Abstract: Newly detected type 2 diabetic patients exhibit a higher degree of early atherosclerosis than normal glucose-tolerant subjects matched for age and sex. Our data suggest that hyperglycemia, together with a clustering of risk factors, and in particular dyslipidemia, may cause intimal-medial thickening in the early phases of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
83
3
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 0 publications
5
83
3
8
Order By: Relevance
“…We did not find any significant correlation with IMT other than increased AG and AIx after adjustment for age and sex (Table 3). This is in line with the results of previous studies, in which the associations of traditional cardiovascular risk factors with IMT were weaker and less consistent in diabetic study cohorts than in non-diabetic cohorts [44,45,[63][64][65]. In a subset of study patients, we observed that an increase in the mineralisation scores was associated with an increase in IMT, AG and peripheral and central systolic and pulse pressures.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We did not find any significant correlation with IMT other than increased AG and AIx after adjustment for age and sex (Table 3). This is in line with the results of previous studies, in which the associations of traditional cardiovascular risk factors with IMT were weaker and less consistent in diabetic study cohorts than in non-diabetic cohorts [44,45,[63][64][65]. In a subset of study patients, we observed that an increase in the mineralisation scores was associated with an increase in IMT, AG and peripheral and central systolic and pulse pressures.…”
Section: Discussionsupporting
confidence: 81%
“…In a smaller study by Brooks et al in which PWA was used, both AG and AIx were increased in diabetic men but not in diabetic women [43]. Likewise, carotid IMT has consistently been shown to be greater in type 2 diabetic patients than in non-diabetic subjects [44][45][46]. In addition, IMT has correlated with the presence of CVD in type 2 diabetic patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that subclinical disease may have developed before the onset of clinical diabetes, assuming that a high percentage of the participants with IGT will ultimately develop clinical diabetes, which is consistent with other studies. 29 The fasting blood glucose levels were a weak predictor of outcomes in the study. Most of the other traditional cardiovascular risk factors were also not significant predictors of the risk of CVD among the diabetics after adjusting for the extent of subclinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this difference is in the same order of magnitude, or even greater, than those reported in studies comparing subjects of similar age with respect to other polymorphisms [21], or comparing subjects with and without vascular risk factors such as diabetes [22] or low HDL-C [23] with their respective healthy controls. Moreover, prospective studies evaluating the capacity of IMT max to predict cardiovascular events showed that moving from the first to the fifth quintile of internal carotid artery IMT max with four steps of about 0.2 mm on average, the relative risk of cardiovascular events increased fourfold [24].…”
Section: Discussionmentioning
confidence: 61%